Estilos de vida y nivel cognitivo del adulto mayor. Centro de Salud Liberación Social - Cabrera Romero, Evelyn Natalie (2020)
Quantitative, descriptive, correlational, cross-sectional research, whose objective was to determine the relationship between the Level of lifestyle and the cognitive level of the elderly who attends the Social Liberation Health Center. The concepts of Lifestyle according to Pender and Cognitive Level according to Carretero et al. The population was made up of 60 older adults, determining a sample of 52. The instruments used were: the Health Promotion Lifestyle Scale (Pender) and the Mini Mental State Test (MMSE) Test (Folstein et al.). For the data analysis, the Kendall Tau B statistical test was applied in the SPSS Version 25 program. The results showed that 60 percent of older adults presented an unhealthy lifestyle level and 40 percent lifestyle levels, healthy; 52 percent presented mild cognitive impairment, 31 percent normal cognitive level, and 17 percent moderate cognitive impairment. In the study, no cases of older adults with severe cognitive impairment were found. Conclusion: there is a significant relationship between the health promoting lifestyle and the cognitive level of the elderly. (p = 0.000).